The spontaneous expression of pride and shame: Evidence for biologically innate nonverbal displays - Tracy, J. L.; Matsumoto, D. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
The present research examined whether the recognizable nonverbal expressions associated with pride and shame may be biologically innate behavioral responses to success and failure. Specifically, we tested whether sighted, blind, and congenitally blind individuals across cultures spontaneously display pride and shame behaviors in response to the same success and failure situations—victory and defeat at the Olympic or Paralympic Games. Results showed that sighted, blind, and congenitally blind individuals from >30 nations displayed the behaviors associated with the prototypical pride expression in response to success. Sighted, blind, and congenitally blind individuals from most cultures also displayed behaviors associated with shame in response to failure. However, culture moderated the shame response among sighted athletes: it was less pronounced among individuals from highly individualistic, self-expression-valuing cultures, primarily in North America and West Eurasia. Given that congenitally blind individuals across cultures showed the shame response to failure, findings overall are consistent with the suggestion that the behavioral expressions associated with both shame and pride are likely to be innate, but the shame display may be intentionally inhibited by some sighted individuals in accordance with cultural norms.